Peran Guru Agama Islam dalam Mencegah Perilaku Intoleransi Siswa - Hendi Perdana; Nurul Latifatul Inayati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in preventing intolerance among students. The method used is descriptive analysis with a literature review approach. In collecting data, the author employed basic observation and advanced note-taking techniques to analyze written data from educational journals, while the note-taking technique was used to obtain relevant information from various sources such as books and articles. The data was analyzed using content analysis, allowing the researcher to describe and relate the data to supporting documents on Islamic religious education. Through this analysis, the research results show that PAI teachers have a strategic role in preventing intolerance by teaching Islamic values such as tolerance, justice, and mutual respect. Teachers serve as role models in shaping students' inclusive character and integrating extracurricular activities to promote harmony. This study concludes that the active role of PAI teachers is crucial in creating a harmonious school environment, and collaboration between teachers, parents, and the school community must be strengthened to support inclusive and sustainable character education.